THE INFLUENCE OF SOCIAL STRESSORS ON JOB PERFORMANCE WITH THE ROLE OF STRAIN AS MEDIATOR IN BTN BOGOR - Ramadhan, Gusti Muhammad (Al-Infaq: Jurnal Ekonomi Islam, 2017)
The focus of this study is to examine the factors that influence job performance of BTN Bogor employees by analyzing several variables namely, interpersonal conflict, organizational politics, and also the potential mediating role of strain between stressors and job performance. This study is using quantitative descriptive analysis. The results showed that interpersonal conflict has significant influence on strain and job performance. However, there was no evidence supporting that organizational politics has significant influence on job performance, and strain as the mediator of stressors and job performance.